Category innovation for facial cleansing/makeup remover wipes using a holistic sensory and consumer research approach in a business environment - Xing, Huajing (Kansas State University, 2019)
Makeup chemistries have evolved over the recent years and have become more long-wear, waterproof and difficult to remove. Thus, many changes have occurred among products designed to remove makeup. Specifically, the facial cleansing/makeup remover wipes category is challenged to establish new strategies and adapt to the changing consumer needs and the evolving competitive landscape. A holistic approach utilizing various sensory and consumer research methodologies was applied to guide product developers for wipe innovation. A global landscape study using a customized Descriptive Analysis method provided objective product profiling for the wipe category review based on thirteen products selected from four global regions. Three conceptual maps generated from this research displayed the similarity and differences among the products in three major areas: visual and tactile, cleansing performance, and skin perception. A consumer design of experiments (DOE) study using a blind, sequential monadic, balanced incomplete block design (BIBD) conducted in the U.S. and U.K. evaluated eighteen prototypes with 4 factor combination (formula, thickness, weight, lotion add-on) of different levels. Based on the results, a simulation model was developed to identify best factor combination with highest purchase intent and overall liking for product optimization. Driver’s analysis, sensitivity analysis, and penalty analysis conducted in this research offered more in-depth understanding on product performance. Lastly based on the data generated from the DOE study and in-vitro lab measurements conducted on the same eighteen prototypes, predictive models between certain consumer perceptible attributes and in-vitro lab measurements using partial least squares (PLS) regression with a cross validation procedure were established to provide rapid methods for facial cleansing/makeup remover wipes prototype screening. Future consumer studies are required to further validate these models...
Keywords: Sensory; Consumer research; Facial cleansing/makeup remover wipes